Enzymatic recovery of glycopeptides from different industrial grades edible bird’s nest and its by-products: nutrient, probiotic and antioxidant activities, and physicochemical characteristics - Hidayati Syamimi Mohd Noor; Rafidah Mohd Ariff; Lee Sin Chang; Xin Yi Chai; Hui Yan Tan; Nur’ Aliah Daud; Abdul Salam Babji; Seng Joe Lim (Food Science and Human Wellness)
This study was conducted to recover edible bird’s nest (EBN) hydrolysates from different grades of EBN, including the industrial by-products, using enzymatic treatment. The nutrient, physicochemical properties and antioxidant activities of the recovered hydrolysates at different hydrolysis times were evaluated. Results showed that the recovery yield of enzymatic hydrolysis was above 89 % for all grades of EBN and the degree of hydrolysis increased over time. Nitrite content (0.321–0.433 mg/L) was below the permissible tolerance level for all samples. Interestingly, the antioxidant activities (DPPH and ABTS scavenging activities and ferric reducing antioxidant powder (FRAP) activity) were significantly higher (P ≤ 0.05) in hydrolysates recovered from EBN by-products (EBNhC and EBNhD) as compared to the high grade EBN hydrolysates (EBNhA and EBNhB). The in-vitro probiotic activity of EBN and its hydrolysates were examined using the probiotic bacterium Lactobacillus plantarum. Evidently, EBN by-products hydrolysate (EBNhD) recorded the highest number of L. plantarum (1.1 × 1011 CFU/mL), indicating that low grade EBN has the potential as prebiotic material that promotes probiotic activity. This study demonstrated the concept of using EBN by-products hydrolysates for various applications, such as functional ingredients with enhanced bioactivities, to improve its economic value.